Benjamin Britten in context - Stroeher, Vicki P.; Vickers, Justin (Composers in context, 2022)
Benjamin Britten, pianist, conductor, educator, composer of a wide range of music from large-scale operas and choral works to string quartets and songs, is acknowledged as a pivotal figure in mid-twentieth-century Britain. This volume explores the contexts for his multi-faceted career and his engagement with his contemporaries in music, art, literature, and film, British musical institutions, royal and governmental entities, and the church, as well as his ground-breaking projects, philosophical and ideological tenets. The book is thematically structured in five parts: Britten's relationships with Peter Pears, his close friends, mentors, and colleagues; musical life in Britain; his interactions with previous and contemporary generations of composers; his professional work with choreographers, librettists, stage designers, and directors; and his socio-cultural, religious, and political environment. The chapters shed light on the many opportunities and challenges of post-war British musical life that shaped Britten's creative output.